Kualitas Audit dan Manajemen Laba pada Perusahaan Manufaktur di Indonesia - Maria Natalia; Meyliana -; Debbianita - (Jurnal Akuntansi, 2017)
AbstractThe purpose for this research is to test the influence of audit quality to earnings management on manufacturing companies in Indonesia. In this research, the measurement of audit quality divided in five proxies: auditor size, auditor specialization industry, auditor opinion, auditor change, and audit timeliness. The measurement is refers to Habbash and Alghamdi (2016) research. This research used secondary data from manufacturing companies’s annual report listed on Indonesia Stock Exchange in 2015. Data analysis method used in this research is multiple linear regression test. The sample used in this research is 73 manufacturing companies. The results showed that the auditor size, auditor specialization industry, auditor opinion, auditor change, and audit timeliness have no effect on earnings management.Keywords: Audit Quality, Auditor Size, Auditor Opinion,  Earnings Management, and Industry Specialization